FACTORS INFLUENCING AWARENESS OF CLIMATE CHANGE AMONG TOMATO FARMERS IN BAUCHI LOCAL GOVERNMENT AREA, BAUCHI STATE, NIGERIA - Ibrahim, U.; Garba, A.S.; Atman, F.M.; Abdullahi, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the Factors influencing awareness of climate change among tomato farmers in Bauchi Local Government Area (LGA) of Bauchi State, Nigeria. Simple random sampling technique was used in selecting 400 tomato producers from the study area. Structured questionnaire was used for data collection. Data were analyzed using descriptive and inferential statistics. The result showed that 30% of the respondents fell within the age category of 40-49 with the mean age of 44 years, had household size of 5-7 persons and had secondary education, respectively. Also, the results revealed that 37.5% of the respondents had farming experience of between of 10 years while 45% had a land size of 2.2 hectares. The findings further revealed that half (50%) of the respondents were somewhat familiar with climate change while 30% were very familiar. Half (50%) of respondents perceived that climate change lead to increase in temperature while 45%, 42% and 40% perceived that it leads to drastic change in weather reduce crop productivity and reduction in soil fertility, respectively. Furthermore, the results indicate that age, marital status, education, farming experience, membership of association, farm size and access to credit were significant at (P<0.01) in influencing the effect of climate change on tomatoes production. it was concluded that tomato farmers exhibit a moderate to high level of awareness regarding climate change, which is influenced by factors such as age, education, and access to information. Based on the finding, it is recommended that farmers should form cooperative societies to facilitate access to financial resources through microfinance institutions, commercial banks and other financial institutions.